PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) BARANG MILIK DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA MANADO - Monica, Sepang Gisella; Saerang, David Paul Elia; Pangerapan, Sonny (Universitas Sam Ratulangi, 2017)
Regional management information system application is a computer application program that is integrated and can help the process of the administration of the local government from the provincial level, city level until the sub-district level. SIMDA consists of 26 separate application that can be distributed to construct the SKPD with Â ntegrated database system so that the output can be used by the regional government to help the decision making process. The purpose of this research is to know the Applying of Regional Management Information System Regional Assets on Financial and Asset Management Agency of the city of Manado. The analysis method used is qualitative descriptive method. The results of the study showed that the applying of the SIMDA-BMD on BPKAD had run well, starting from planning, procurement, use, administration, utilization, maintanence and deletion are well under way, but there is a weakness in this application which cannot be used on windows 10.Keywords: Regional Management Information System, Regional Assets.